RF circuit design - Bowick, Chris (Newnes/Elsevier, 2008)
Finally, a new edition of the classic RF circuit design book. RF circuit design now more important that ever in the wireless world in which we live. In most of the wireless devices that we use there is an RF component and this book tells the reader how to design and integrate that component in a very practical fashion. This classic book is being updated form a "wire lead," discrete components-Smith charts book to one that covers today's IC and system-level design issues. Computer software usages replaces many of the hand calculation, which have been moved to the appendices for reference. Newer device and package issues (SMT) have also been included, as have board-level signal integrity issues. *Completely updated but still contains its classic timeless information *Two NEW chapters on RF Front-End Design and RF Design Tools *Not overly math intensive, perfect for the working RF and digital professional that need to build analog-RF-Wireless circuits